1991
DOI: 10.1073/pnas.88.3.874
|View full text |Cite
|
Sign up to set email alerts
|

Root communication among desert shrubs.

Abstract: Descriptive and experimental studies of desert shrub distributions have revealed important questions about the mechanisms by which plants interact. For example, do roots interact by mechanisms other than simple competition for limiting resources? We investigated this question using the desert shrubs Ambrosia dumosa and Larrea tridentata grown in chambers that allowed observation of roots during intraplant and intra-and interspecific interplant encounters. Two types of root "communication" were revealed. Ambros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
192
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(208 citation statements)
references
References 15 publications
13
192
1
2
Order By: Relevance
“…Individual root recognition has been predominantly identified in experiments showing that the root tip growth of a plant responds differently when the plant runs into the roots of another plant than when it runs into its own roots, i.e. self/non-self (S/NS) root discrimination (Mahall & Callaway 1991;de Kroon et al 2003). A plant's ability to distinguish its own roots should be an inherent skill, because root growth occurs in a remarkably heterogeneous space (Hodge 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Individual root recognition has been predominantly identified in experiments showing that the root tip growth of a plant responds differently when the plant runs into the roots of another plant than when it runs into its own roots, i.e. self/non-self (S/NS) root discrimination (Mahall & Callaway 1991;de Kroon et al 2003). A plant's ability to distinguish its own roots should be an inherent skill, because root growth occurs in a remarkably heterogeneous space (Hodge 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Mahall and Callaway [14][15][16] found that roots of the desert shrub Ambrosia dumosa responded to contacts with roots of different Ambrosia plants by decreasing their rate of elongation, but showed no such response when contacting other roots of the same individual plant. By contrast, Falik et al 17 have shown that roots of Pisum sativum decreased root growth in the presence and in the direction of their own roots compared to roots of other plants.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the outcome of belowground interactions between plants, of the kind illustrated in the previous set of examples, can be mediated by identity recognition, including species-specific responses (23)(24)(25)(26), kin/stranger responses (27)(28)(29)(30), and self/nonself responses (2, 3). Mahall and Callaway (23) found that root systems of the desert shrub Ambrosia dumosa appear to be capable of detecting and avoiding other Ambrosia root systems.…”
mentioning
confidence: 99%
“…Mahall and Callaway (23) found that root systems of the desert shrub Ambrosia dumosa appear to be capable of detecting and avoiding other Ambrosia root systems. In contrast, roots of another desert shrub species, Larrea tridentata, inhibit both Larrea and Ambrosia roots in their vicinity.…”
mentioning
confidence: 99%